Progression of palindromic rheumatism to juvenile idiopathic arthritis in a Japanese girl carrying heterozygous L110P-E148Q substitutions of MEFV gene. Issue 2 (4th March 2018) - Kobayashi, Ichiro; Yamazaki, Yasuhiro; Tozawa, Yusuke; Ueki, Masahiro; Takezaki, Shunichiro; Yamada, Masafumi; Ariga, Tadashi
Abstract: Palindromic rheumatism (PR), a rare disease in children, is characterized by recurrent arthritis or periarthritis and asymptomatic interval. We report evolution of PR to juvenile idiopathic arthritis in a Japanese girl with heterozygous complex L110P-E148Q allele of MEFV gene. Poor response to colchicine alone suggests that the MEFV substitution could increase the susceptibility to arthritis rather than caused arthritis associated with atypical Familial Mediterranean Fever. Weekly methotrexate is a choice for such cases.